A comprehensive promoter landscape identifies a novel promoter for CD133 in restricted tissues, cancers, and stem cells - Sompallae, Ramakrishna; Hofmann, Oliver M.; Maher, Christopher A.; Gedye, Craig; Behren, Andreas; Vitezic, Morana; Daub, Carsten O.; Devalle, Sylvie; Caballero, Otavia L.; Carninci, Piero; Hayashizaki, Yoshihide; Lawlor, Elizabeth R.; et al. (Frontiers in Genetics, 2013)
PROM1 is the gene encoding prominin-1 or CD133, an important cell surface marker for the isolation of both normal and cancer stem cells. PROM1 transcripts initiate at a range of transcription start sites (TSS) associated with distinct tissue and cancer expression profiles. Using high resolution Cap Analysis of Gene Expression (CAGE) sequencing we characterize TSS utilization across a broad range of normal and developmental tissues. We identify a novel proximal promoter (P6) within CD133+ melanoma cell lines and stem cells. Additional exon array sampling finds P6 to be active in populations enriched for mesenchyme, neural stem cells and within CD133+ enriched Ewing sarcomas. The P6 promoter is enriched with respect to previously characterized PROM1 promoters for a HMGI/Y (HMGA1) family transcription factor binding site motif and exhibits different epigenetic modifications relative to the canonical promoter region of PROM1.